Structural Studies of 2-Pentyl/Pentenyl-Substituted Methyl 4-Hydroxy-2H-1,2-Benzothiazine-3-Carboxylate-1,1-Dioxide - Muhammad Nadeem ARSHAD; Muhammad ZIA-UR-REHMAN; Islam Ullah KHAN; Ghulam MUSTAFA; Muhammad SHAFIQ; Hafiz Muhammad RAFIQUE; Kevin Travis HOLMAN (Walailak Journal of Science and Technology, 2012)
Crystal structures of methyl 2-pentyl-4-hydroxy-2H-1,2-benzothiazine-3-carboxylate-1,1-dioxide 1 and methyl 2-pentenyl-4-hydroxy-2H-1,2-benzothiazine-3-carboxylate-1,1-dioxide 2 have been determined after their synthesis from saccharin. 1 and 2 crystallize in a monoclinic and orthorhombic crystal system, respectively. The asymmetric unit of both contains one molecule of each compound and shows intramolecular O-H×××O interactions generating six membered ring motifs S11(6). Intermolecular hydrogen bonding interactions have been observed in the molecule with the pentyl side chain. The thiazine ring in both molecules adopts a half chair conformation with a r.m.s. deviation of 0.2049 Å and 0.2161 Å.